Clinical Terminologies in the NHS: SNOMED CT and dm+d - Ian Spiers; Jo Goulding; Ian Arrowsmith (University of Huddersfield Press, 2017)
Clinical terminologies are fundamental to the successful recording of clinical data within Electronic Health Record systems and are important in enabling the sharing of data between systems. An overview of the structure and benefits of the international terminology SNOMED CT and the NHS dictionary of medicines and devices (dm+d) are described. Also discussed is a history of clinical terminologies used within the NHS.